2023
DOI: 10.3390/jof9111044
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Systematics and Taxonomic Analyses of Three New Wood-Inhabiting Fungi of Hyphoderma (Hyphodermataceae, Basidiomycota)

Yang Yang,
Qianquan Jiang,
Qi Li
et al.

Abstract: In this present study, three new wood-inhabiting fungal taxa, Hyphoderma niveomarginatum, H. sordidum and H. weishanense, are proposed. Hyphoderma niveomarginatum is characterized by the ceraceous basidiomata having a smooth, cracking hymenial surface and the presence of the moniliform cystidia and ellipsoid basidiospores (7–9 × 3.5–5 µm). Hyphoderma sordidum is characterized by its resupinate basidiomata with a smooth hymenial surface with the fimbriate margin, the presence of the tubular cystidia and ellipso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Based on the phylogenetic and morphological research results, more and more new wood-inhabiting fungi are being found and reported [ 1 , 43 , 54 , 55 , 89 , 90 , 91 , 92 ]. In the present study, four new taxa from the subtropics are described based on morphological and molecular phylogenetic analyses, which can enrich the wood-inhabiting fungal diversity in China and the world.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the phylogenetic and morphological research results, more and more new wood-inhabiting fungi are being found and reported [ 1 , 43 , 54 , 55 , 89 , 90 , 91 , 92 ]. In the present study, four new taxa from the subtropics are described based on morphological and molecular phylogenetic analyses, which can enrich the wood-inhabiting fungal diversity in China and the world.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they are important strategic biological resources [ 49 , 50 ]. Wood-inhabiting fungi are an extensively studied group of Basidiomycota, but their diversity is still unknown in China, where many of the recently described taxa of this ecogroup were found [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. Based on morphological and molecular phylogenetic analysis, we described five new species from Yunnan Province, China.…”
Section: Discussionmentioning
confidence: 99%
“…The CTAB rapid plant genome extraction kit-DN14 (Aidlab Biotechnologies Co., Ltd., Beijing) was used to obtain DNA from dried specimens and PCR was performed according to the manufacturer’s instructions with some modifications ( Yang et al 2023 ). ITS were amplified using the primer pairs ITS5/ITS4 ( White et al 1990 ).…”
Section: Materials and Methodsmentioning
confidence: 99%